Curbside consultation in IBD : 49 clinical questions - Rubin, David T., 1968-; Friedman, Sonia; Farraye, Francis A. (Curbside consultation in gastroenterology., 2015)
"Are you looking for concise, practical answers to questions that are often left unanswered by traditional inflammatory bowel disease (IBD) references? Are you seeking brief, evidence-based and updated advice for complicated cases or complications? Curbside Consultation in IBD: 49 Clinical Questions, Second Edition provides quick and direct answers to the thorny questions commonly posed during a "curbside consultation" between colleagues. Dr. David T. Rubin, Dr. Sonia Friedman, and Dr. Francis A. Farraye are joined by a world-class group of contributors on the Second Edition, which offers expert advice, preferences, and opinions on tough clinical questions commonly associated with IBD. The unique Q&A format provides quick access to current information related to IBD with the simplicity of a conversation between two colleagues. Numerous images, diagrams, and references are included to better illustrate IBD. Some of the questions that are answered inside the Second Edition include: - How can I clarify the diagnosis in my patient with indeterminate colitis? - What is the role of concomitant immunomodulators with biologic use in IBD? - When in the treatment algorithm should methotrexate be considered for Crohn's disease? Is there a role for low-dose methotrexate in the prevention of immunogenicity? - How should we be using fecal markers such as lactoferrin and calprotectin in our patients? - Should I use chromoendoscopy in my surveillance colonoscopy in IBD? How and which agent? - What is the updated approach to antimetabolites and biologic therapy in IBD and pregnancy? - When should I consider anti-integrin therapy for my patient with IBD?"--Provided by publisher.